Long COVID symptoms in hospital employees after post-vaccination SARS-CoV-2 infection in Austria: A study on self-reported incidence and associated factors. Issue 4 (April 2023) - Brunner-Ziegler, Sophie; Bäuerle, Martin; Brühl, Peter; Kornek, Gabriela; Parschalk, Bernhard; Savic, Rebeka; Schnetzinger, Maximilian; Spath, Tibor; Straßl, Robert Paul; Handisurya, Alessandra; Thalhammer, Florian
Abstract: Purpose: Post acute sequelae of SARS-CoV-2 infection are defined by persistence or re-occurrence of symptoms six to 12 weeks after SARS-CoV-2 infections. Methods: Twice vaccinated hospital employees after mild to moderate post-vaccination SARS-CoV-2 infection completed a questionnaire on the incidence of general, respiratory, neuropsychiatric, dermatological and gastrointestinal symptoms, experienced during their acute infection and eight weeks after recovery. Post acute sequelae of SARS-CoV-2 infection were analysed in relation to socio-demographic-, health-, virus- and acute infection-related characteristics. Results: 73 participants, 25 women and 48 men with a mean age of 40.9 years, with a post-vaccination SARS-CoV-2 infection completed the survey. Out of these 93 % reported at least one symptom at time of initial SARS-CoV-2 infection, 31.5 %, predominantly women, reported post acute sequelae at least eight weeks after the acute infection stage. Fatigue, dysgeusia and dysosmia, headache or difficulty concentrating and shortness of breath during acute infection, BMI> 25 and pre-existing pulmonary disorders were associated with post acute sequelae of SARS-CoV-2 infection. Participants with initially more than five symptoms were four times more likely to report post acute sequelae. Conclusion: It is suggested that the multiplicity of symptoms during acute SARS-CoV-2 infections increases the risk for post acute symptoms.